Identifying the possibility of using unmanned aerial vehicles in the process of construction projects implementation - Agnieszka Waniewska (Scientific Journal of the Military University of Land Forces, 2020)
Contemporary dynamic development in the field of modern technologies affects the development of unmanned aerial vehicles. The potential application area of this type of technology is constantly growing. The equipment is available to almost everyone and its use is becoming ever easier. The aim of the article is to present the possibility of using unmanned aerial vehicles in construction projects, for economic and time reasons, as well as to perform work in places that are inaccessible or too dangerous for humans. The article is the result of literature research, expert opinions and author’s own analyses. The article draws attention to the fact that unmanned aerial vehicles may have a number of applications and unlimited possibilities. The use of modern technologies enables flights at different heights and within many kilometers. Due to the fact that they are equipped with various types of cameras, they constitute a useful observation tool in various projects. The authors of the article conduct research on the wide application of unmanned aerial vehicles in construction projects.